(untitled) (Journal of Dhaka Medical College, 2015)
Peutz-Jeghers syndrome is characterized mainly by the presence of hamartomatous polyposis of gastrointestinal tract and melanin spots on the lips and buccal mucosa. The polyps are mostly found in the small bowel and less frequently seen in the stomach and colon. Intestinal polyps in short term may cause chronic bleeding, intestinal occlusion and intussusceptions. There is small but significant risk of small bowel adenocarcinoma, cancer of pancreas, breast, ovary and endometrium. A case of peutz-jeghers syndrome was presented with a complaint of episodes of colicky abdominal pain and vomiting; small bowel intussusception was diagnosed and an operation was performed in Colorectal Surgery unit of Bangabandhu Sheikh Mujib Medical University (BSMMU) Hospital, Dhaka, jejuno-ileo-caecal polyps were removed by enterotomy. On discharge she was instructed to attend our unit four weeks later for colonoscopic removal of sigmoid polyps and also advised to attend breast and cervical screening program. DOI: http://dx.doi.org/10.3329/jdmc.v23i1.22714 J Dhaka Medical College, Vol. 23, No.1, April, 2014, Page 147-150